Prospects and retrospects of plant bioprospecting in Nepal with special reference of medicinal and aromatic plants (MAPs) - Gautam, L. N.; Shakya, D. M. (Journal of Plant Resources, 2008)
Bioprospecting has primary economic purposes (e.g., new drugs, crops, industrial products). It entails the research and exploration of biodiversity for commercially and economically valuable genetic and biochemical resources of MAPs. Biodiversity of Nepal is unique and richest within its small territory. The impetus for bioprospecting came from a growing realization that the plant resources of Nepal are depleting rapidly due to over exploitation and unsustainable practices. Legal tools are being developed whereby developing countries and other biodiversity rich countries may exert greater leverage over the use of the resources that can be used to earn revenues, promote conservation, and train and educate the multidisciplinary experts. Based on the ethno botanical information and public demand, the laboratory prospects certain MAPs for phytochemical and biological studies. It not only expands the skills of Nepalese scientists but also benefits local communities that drawn their skills and knowledge by growing public demand for plant based products. Bio-prospecting can lead to substantial increases in value of natural resources. Therefore, this paper seeks to provide previous and future of biodiversity prospecting in Nepal. Key words: Bio-Prospecting, Medicinal and Aromatic Plants (MAPs), Conservation, Standardization, Sustainable use, Economic value of marginal species, Indigenous knowledge, Convention of Biological Diversity (CBD).